2010
DOI: 10.1007/s00134-010-1927-0
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the critically ill patient: a double blind, randomized, placebo-controlled trial

Abstract: Although numerous uncertainties remain (type and the number of strains to use, delay and length of administration), and despite an acceptable safety profile, the daily prophylactic administration of probiotics cannot be encouraged in the critically ill patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(191 citation statements)
references
References 18 publications
(30 reference statements)
3
178
1
9
Order By: Relevance
“…However, the conclusion of the meta-analysis was challenged because of the selection methodology ( Van Silvestri 2010). More recently, three additional RCTs were published demonstrating that probiotics are safe and efficacious in preventing VAP in ICUs (Barraud 2010;Tan 2011). Therefore, we aim to summate the results of all available data systematically to generate the best evidence for the prevention of VAP.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conclusion of the meta-analysis was challenged because of the selection methodology ( Van Silvestri 2010). More recently, three additional RCTs were published demonstrating that probiotics are safe and efficacious in preventing VAP in ICUs (Barraud 2010;Tan 2011). Therefore, we aim to summate the results of all available data systematically to generate the best evidence for the prevention of VAP.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Six studies found instances of probiotic-related infection. Four studies used a probiotic formula (Barraud 2010;Forestier 2008;Klarin 2008;Tan 2011), and two studies used a synbiotic formula (Knight 2009;Kotzampassi 2006;Spindler-Vesel 2007), i.e. Synbiotic 2000FORTE.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Tolerability of lactobacilli based probiotics has been demonstrated [12][13][14][15] and compliance of 75-85% has been observed [1,15] in studies of bacterial pathogens Furthermore, a two-year trial on the effects of VSL#3 on C. difficile associated diarrhea showed the probiotic was well tolerated though issues with adherence occurred, for reasons similar to our findings [15]. In a recent trial examining the acceptability and tolerance of probiotics for patients with carriage by Methicillinresistant Staphylococcus aureus, we found that the chosen probiotic (L. rhamnosus HN001) was well tolerated [16].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the National Healthcare Safety Network at the Centers for Disease Control and Prevention show that in 2009-2010, 13.9% of bacterial healthcare-associated infections (HAIs) were caused by Enterococcus species, including VRE. Ninety percent of VRE are E. faecium species [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prophylactic administration of probiotics has been associated with increased mortality in septic patients (56), so care should be taken before introducing probiotic regimens to severely ill patients. However, sepsis from a probiotic strain such as Lactobacillus remains very unlikely (57), even in at-risk patients.…”
Section: Ibdmentioning
confidence: 99%